Flavor release by enzymatic hydrolysis of starch samples containing vanillin-amylose inclusion complexes - Rodríguez, Silvio David (2014)
Hylon VII is a high amylose corn starch which has excellent gelling properties, and its behavior as flavor encapsulant is relevant to the food industry because its ability to regulate a swelling-controlled release in aqueous media. We studied the release of vanillin, encapsulated in Hylon VII under experimental conditions in which the amylose–vanillin inclusion complex is obtained, along with the enzymatic hydrolysis of the starch carried out using salivary amylase of human origin. The flavor release into the aqueous phase was quantified spectrophotometrically and the partition into the headspace was assessed by a gas sensor array. Simultaneously, the progress of the enzymatic reaction was determined by analysis of reducing sugars. The release of flavor into the aqueous phase followed a diffusion/relaxation kinetic, whereas the headspace analysis showed an increase in the aroma intensity according to the increase of reducing sugars concentration in the solution. Furthermore, by using the Unfolded Cluster Analysis methodology it was possible to accurately discriminate the samples corresponding to each of the assayed hydrolysis times. The joint detection of the flavor in the condensed phase and in the headspace compared with the degree of starch hydrolysis provides an overall analytical painting of a daily food intake process.